Progress in the integration of ChatGPT in Higher Education: an examination of applications, advantages, and challenges - Leopoldo Vinicio Venegas Loor; Paola v Moreira Aguayo; Alberto Rodríguez Rodríguez (Serie Científica de la Universidad de las Ciencias Informáticas)
Artificial intelligence (AI), especially natural language processing models such as ChatGPT, is transforming higher education. The current literature indicates several uses of ChatGPT in this domain, including virtual tutoring, educational material generation, and automated evaluation. A significant advantage is the capacity to personalize education, tailoring it to the specific requirements of students and offering study suggestions derived from performance data analysis. Furthermore, ChatGPT aids educators in handling substantial workloads by providing automatic feedback on assignments and assessments, so liberating time for more significant instructional endeavors. Nonetheless, the deployment of ChatGPT has obstacles, including maintaining objectivity in automated assessments and safeguarding student data privacy. Addressing these difficulties necessitates stringent validation of model performance and the establishment of explicit data privacy regulations. By doing a critical examination of case studies and evaluating prior research, one can attain a comprehensive grasp of how ChatGPT can be effectively utilized to improve teaching, learning, and assessment in academic environments. Its capacity to understand and produce content organically renders it particularly adept at engaging with students and delivering tailored responses to their distinct educational requirements.